Power and Translation: A Study of Multilingual Signs in Lombok - Shulhan Syaia; Baharuddin; Lalu Jaswadi Putera (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study examines the representation of power and translation practices in multilingual outdoor signage on Gili Trawangan as an international tourist destination. The study employs a descriptive qualitative approach grounded in Linguistic Landscape Studies and Postcolonial Translation Studies to analyze language use, translation strategies, and visual composition in multilingual signs. Data were collected in September 2025 through observation, documentation, recording, and data selection. A total of 35 permanent and semi-permanent public signs located on main roads, beachfront areas, restaurants, hotels, shops, and tourist information centers were analyzed using discourse analysis and a postcolonial translation approach. The analysis involved categorization of signs, visual and linguistic examination, and translation assessment. Validity was strengthened through data triangulation with field observation notes and contextual tourism information. The findings reveal a clear linguistic hierarchy within the tourism landscape of Gili Trawangan. Indonesian dominates institutional signage, while English strongly dominates commercial signs as symbolic capital aimed at attracting international tourists. Sasak, the local language, appears only minimally and functions largely as a symbolic cultural marker. The study also identifies literal translation patterns in regulatory signs and adaptive translation in commercial signage. In addition, visual composition reinforces the dominance of English through larger font sizes, strategic text placement, and stronger visual emphasis. This study concludes that multilingual signage functions not only as a medium of information, but also as a representation of power relations and the marginalization of local identity within the global tourism space.